Variations in childbirth interventions in high-income countries: protocol for a multi-national cross-sectional study - Seijmonsbergen-Schermers, Anna; de Jonge, Ank; van den Akker, Thomas; Beeckman, Katrien; Bogaerts, Annick; Barros, Monalisa; Janssen, Patricia; Binfa, Lorena; Rydahl, Eva; Frith, Lucy; Gross, Mechthild; Hálfdánsdóttir, Berglind; et al. (My University, 2018)
Introduction: There are growing concerns about the increase in rates of commonly used childbirth interventions. When indicated, childbirth interventions are crucial for preventing maternal and perinatal morbidity and mortality, but their routine use in healthy women and children leads to avoidable maternal and neonatal harm. Establishing ideal rates of interventions can be challenging. This study aims to describe the range of variations in the use of commonly used childbirth interventions in high-income countries around the world, and in outcomes in nulliparous and multiparous women. Methods and analysis: This multinational cross-sectional study will use data from births in 2013 with national population data or representative samples of the population of pregnant women in high-income countries. Data from women who gave birth to a single child from 37 weeks gestation onwards will be included and the results will be presented for nulliparous and multiparous women separately. Anonymised individual level data will be analysed. Primary outcomes are rates of commonly used childbirth interventions, including induction and/or augmentation of labour, intrapartum antibiotics, epidural and pharmacological pain relief, episiotomy in vaginal births, instrument-assisted birth (vacuum or forceps), caesarean section and use of oxytocin postpartum. Secondary outcomes are maternal and perinatal mortality, Apgar score below 7 at 5 min, postpartum haemorrhage and obstetric anal sphincter injury. Univariable and multivariable logistic regression analyses will be conducted to investigate variations among countries, adjusted for maternal age, body mass index, gestational weight gain, ethnic background, socioeconomic status and infant birth weight. The overall mean rates will be considered as a reference category, weighted for the size of the study population per country. Ethics and dissemination: The Medical Ethics Review Committee of VU University Medical Center Amsterdam confirmed that an official approval of this study was not required. Results will be disseminated at national and international conferences and published in peer-reviewed journals.
PUBLISHED
Keywords: Childbirth; Interventions; Intrapartum; Labour; Birth; Variations; Cross-sectional study; CHILDBIRTH; Childbirth/Labour/Intrapartum; INTERVENTIONS; Mode of birth